Assessing Spectral Similarities between Rainfed and Irrigated Croplands in a Humid Environment for Irrigated Land Mapping. (June 2014) - Shamal, S.A.M.; Weatherhead, Keith
Deriving accurate spatial assessments of the distribution of irrigated crops has become more important in recent years for water resource planning, particularly where irrigation water resources are constrained. However, this is easier in arid climates than in humid areas such as eastern England. The challenges in using alternative vegetation indices derived from remote sensing to discriminate between irrigated and rainfed crops in a humid climate are described, focusing on potato (Solanum tuberosum L.), the most important irrigated crop in England. Three techniques were evaluated: (a) temporal profile comparisons using the Normalized Difference Vegetation Index (NDVI); (b) cluster analysis combining the NDVI and the Normalized Difference Water Index (NDWI); and (c) identifying differences in chlorophyll content using green and near infrared bands. However, the study confirmed that the spectral signatures of irrigated and rainfed potato in England during a typical summer are very similar, presumably due to frequent rainfall events which reduce differences in water stress and chlorophyll content. The implications for using remote sensing to estimate irrigated areas in humid climates are discussed.